ANALISIS ARTIKULASI LAPORAN KEUANGAN PEMERINTAH DAERAH - Mohamad Ahlal Firdaus (ABIS: Accounting and Business Information Systems Journal, 2015)
This research aims to analyse the articulation of sixty six unqualified opinion of local government financial statements (LKPD) for fiscal year year 2014 in Java and Bali. This research also identify types of inarticulatory when a LKPD is in inarticulate condition. This research utilizes descriptive qualitative approach and uses documentation technique for data collection. The analysis is employed by comparing the fact on the face (lembar muka) of LKPD with the criteria in accordance to accounting equation and Government Accounting Standard (SAP). Identification of inarticulatory is performed using documentation technique through a deep information extracting from audited result report BPK RI. The results of articulation assessment show that most of LKPD (89,39%) are not articulate, on average level of artikculation is 82,67%. Furthermores, identification results of inarticulatory types show there are twelve types of inarticulatory with 97 cases on cash toward accrual based LKPD and 10 types of inarticulatory with 24 cases on accrual based LKPD.